Continuous mode operation of microbial fuel cell (MFC) stack with dual gas diffusion cathode design for the treatment of dark fermentation effluent. (28th September 2015) - Pasupuleti, Suresh Babu; Srikanth, Sandipam; Venkata Mohan, S.; Pant, Deepak
Abstract Three microbial fuel cells (MFC) with dual gas diffusion cathode design were operated individually in different operation modes, viz., batch (MFC-BM), semi-continuous (MFC-SCM) and continuous (MFC-CM), using dark fermentation effluent (DFE). MFC-BM depicted lower power density (PD, 1.31 ± 1.75 mW/m2) due to the electron losses and mass transfer limitations, while, MFC-SCM (19.06 ± 2.01 mW/m2) and MFC-CM (15.53 ± 2.51 mW/m2) depicted higher PD. Though MFC-SCM showed higher power output, the energy conversion efficiency (ECE) was higher during MFC-CM (9.85 ± 1.02%) operation over MFC-BM and MFC-SCM operations. Henceforth, the stacking approach was carried out in continuous mode operation using DFE which showed a very good power output along with treatment efficiency. Stack mode operation was carried out at decreasing external loads to increase the overall power output as well as the electron delivering ability of the biocatalyst. Stack MFC depicted its maximum PD (3163 mW/m3; 19.79 mW/m2), across 2 kΩ of external resistance (Rex) along with the treatment efficiency of 80 ± 2%. Further decrement in Rex to 1 kΩ has resulted in lower and unstable PD, due to the inability of the biocatalyst to meet the electron requirement by the circuit. A detailed understanding of the stack MFC was made in terms of electrogenesis, electron discharge, coulombic and energy conversion efficiencies as well as the bioprocess parameters.